A mouse model of the schizophrenia-associated 1q21.1 microdeletion syndrome exhibits altered mesolimbic dopamine transmission. Issue 11 (November 2017) - Nielsen, Jacob; Fejgin, Kim; Sotty, Florence; Nielsen, Vibeke; Mørk, Arne; Christoffersen, Claus; Yavich, Leonid; Lauridsen, Jes; Clausen, Dorte; Larsen, Peter; Egebjerg, Jan; Werge, Thomas; et al.
Abstract 1q21.1 hemizygous microdeletion is a copy number variant leading to eightfold increased risk of schizophrenia. In order to investigate biological alterations induced by this microdeletion, we generated a novel mouse model (Df(h1q21)/+) and characterized it in a broad test battery focusing on schizophrenia-related assays.Df(h1q21)/+ mice displayed increased hyperactivity in response to amphetamine challenge and increased sensitivity to the disruptive effects of amphetamine and phencyclidine hydrochloride (PCP) on prepulse inhibition. Probing of the direct dopamine (DA) pathway using the DA D1 receptor agonist SKF-81297 revealed no differences in induced locomotor activity compared to wild-type mice, butDf(h1q21)/+ mice showed increased sensitivity to the DA D2 receptor agonist quinpirole and the D1/D2 agonist apomorphine. Electrophysiological characterization of DA neuron firing in the ventral tegmental area revealed more spontaneously active DA neurons and increased firing variability inDf(h1q21)/+ mice, and decreased feedback reduction of DA neuron firing in response to amphetamine. In a range of other assays, Df(h1q21)/+ mice showed no difference from wild-type mice: gross brain morphology and basic functions such as reflexes, ASR, thermal pain sensitivity, and motor performance were unaltered. Similarly, anxiety related measures, baseline prepulse inhibition, and seizure threshold were unaltered. In addition to the central nervous system-related phenotypes, Df(h1q21)/+ mice exhibited reduced head-to tail length, which is reminiscent of the short stature reported in humans with 1q21.1 deletion. With aspects of both construct and face validity, theDf(h1q21)/+ model may be used to gain insight into schizophrenia-relevant alterations in dopaminergic transmission.